Pelatihan dan Pendampingan Sadar Bahasa Pada Jurnalis Muda Jambi Melalui Pendekatan ABCD - Mislan,; Wahyuningtyas, Ika Panggih; Santi, Chandri Febri; Solvera, Esy (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2025)
The ability to make news for a journalist must also be in line with his ability to use language as the main media in journalism. The language used in journalism is called journalistic language. Journalistic language should use good and correct Indonesian language rules in accordance with EYD Revision V. This service activity is aimed at providing writing training and language awareness assistance to the Jambi press student community, especially in the fields of EYD usage, word selection, and sentence effectiveness. This service method uses the ABCD Asset Based Communiy Development approach where this approach is based on existing assets, strengths and potentials that underlie the service objectives by analyzing the problems that arise through community service programs in language awareness assistance. The results of the activity show that language awareness training and coaching can improve the journalistic competence of Jambi young journalists in producing more quality journalistic products.